Development of a technology of isothermal annealing with the use of the forging heat for chromium‑molybdenum steel - Roman Kuziak; Artur Barełkowski (Materials & Design, 2021)
The article discusses the results of investigations performed during a thermo-mechanical treatment of forgings made of chromium‑molybdenum 42CrMo4 grade steel. The treatment was realized during a regular series production. The forging process was combined with a heat treatment carried out directly after forging on a specially adapted station. Such a production technology will make it possible to eliminate the step of repeated heating of the forgings. On the example of an element of a steering gear, it was demonstrated how it is possible to perform an isothermal annealing process starting from the temperature at which the trimming of the forgings ends. During the cooling of the forgings, it is enough to maintain the temperature at the proper level in order for the exothermal phase transformation of austenite into pearlite to take place. The test results show that, with the properly selected temperature of isothermal annealing, it is possible to obtain an equilibrial ferritic-pearlitic structure in the required hardness scope. Introducing such a solution into the industrial practice would allow savings more than 80% of the energy used for the heat treatment of forging in this case.